Addition of Dexmedetomidine Prolongs Duration of Vasodilation Induced by Sympathetic Block With Mepivacaine in Dogs. Issue 4 (1st July 2004) - Tezuka, Masatomo; Kitajima, Toshimitsu; Yamaguchi, Shigeki; Kimura, Yoshiyuki; Hamaguchi, Shinsuke
Abstract : Background and Objectives: The aim of this study was to examine the duration of vasodilation induced by sympathetic block with the addition of dexmedetomidine to mepivacaine. Methods: We measured right and left brachial artery blood flow (BABF) before and after stellate ganglion block used as a sympathetic block in dogs. The experimental protocol was designed as follows: (1) left stellate ganglion block using 1.0 mL 0.5% mepivacaine (n = 8), (2) left stellate ganglion block using the addition of dexmedetomidine 0.5 μg to 1.0 mL 0.5% mepivacaine (n = 8), and (3) left stellate ganglion block using the addition of dexmedetomidine 0.5 μg to 1.0 mL physiological saline solution (n = 8). Results: Left stellate ganglion block with mepivacaine alone increased left BABF significantly from 5 minutes through 50 minutes after the block (baseline, 100%; peak at 10 minutes after SGB, 181 ± 27%; P < .01). Left stellate ganglion block with the addition of dexmedetomidine to mepivacaine induced a significant increase of left BABF from 5 minutes through 90 minutes after the block (baseline, 100%; peak at 10 minutes after SGB, 174 ± 36%; P < .01). Left and right BABF did not change significantly after stellate ganglion block with dexmedetomidine only. Right BABF decreased significantly after left stellate ganglion block with mepivacaine alone or the addition of dexmedetomidine to mepivacaine throughout the study. Conclusions: The addition of dexmedetomidine prolongs the duration of vasodilation induced by stellate ganglion block with mepivacaine used for sympathetic block in dogs.